Pain Prevalence in a Pediatric Hospital: Raising Awareness during Pain Awareness Week - Denise Harrison; Cynthia Joly; Christine Chretien; Sarah Cochrane; Jacqueline Ellis; Christine Lamontagne; Vaillancourt Regis (Pain Research and Management)
BACKGROUND: Despite the evidence and availability of numerous validated pain assessment tools and pain management strategies for infants and children, their use remains inconsistent in clinical practice.